Is It Real?: Experiencing Entrepreneurship in Only 30 Minutes. (2nd July 2022) - Fleck, Emma; Teckchandani, Atul; Winkel, Doan
The Is It Real? exercise gives students a glimpse into the entrepreneurial experience by prompting them to have a brief experience with and reflect on the pressures, constraints, and incentives of new business creation. Given that entrepreneurship education encourages the creation of more ventures, and generally encourages students to act entrepreneurially, this exercise helps students understand the importance of the opportunity formation process and ethical decision-making under pressure. Through a 30-minute moneymaking competition, completed in small teams, students develop an appreciation for the variety of business models, the benefit of creating sustainable revenue streams, and the importance of doing business in an ethical way. The debriefing following the exercise gives students an opportunity to reflect on these activities and learn from the experiences of others in the class, building knowledge of the entrepreneurial experience.